CRITICAL FACTORS THAT AFFECTING ADOPTION OF E-LEARNING BASED ON CLOUD COMPUTING FOR IRAQI HIGHER EDUCATION ORGANIZATIONS - Abdulsaeed, Ali A.; Mohd Aboobaider, Burhanuddin; Abd Ghani, Mohd Khanapi; Jaber, Mustafa Musa (ScienceScholar, 2022)
Cloud computing-based e-learning is one of the most popular techniques discovered to promote traditional instruction by software applications and a virtual learning environment. There are many factors that could be regarded in a company's effort to implement or embrace new technology initiatives. As in the literature, many scientists and researchers have particularly explored the factors that influence the adoption of cloud computing along with e-learning issues based on cloud computing that are derived from standards models such as Technology-Organization-Environment (TOE) framework and Technology Acceptance Model (TAM). The aim of the study is to identify critical factors that impact the adoption of cloud computing-based e-learning for Iraqi higher education organizations. Indeed, we identified the 14 critical factors that affect cloud computing uptake for e-learning system in higher education organizations such as compatibility, complexity, cost saving, security and privacy, integrity, and etc. This research examines the ideas and literature used to examine adoption of cloud computing to define future variables that may influence the adoption of cloud computing.